Pegylated interferon-based treatment in patients with advanced liver disease due to chronic delta hepatitis - Gökhan KABAÇAM; George N. DALEKOS; Yılmaz ÇAKALOĞLU; Kalliopi ZACHOU; Thomas BOCK; Andreas ERHARDT; Stefan ZEUZEM; Fehmi TABAK; Kendal YALÇIN; A. Mithat Bozdayı; et al. (Turkish Journal of Gastroenterology, 2019)
-